2016
DOI: 10.1002/pbc.26342
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Doppler in hemoglobin SC disease

Abstract: These results suggest that a different cut-off value for abnormal TCD velocities could be considered for patients with HbSC. Additional studies are warranted to determine the actual risk of stroke in HbSC genotype associated with this possible TCD risk value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Vieira and colleagues [ 10 ] defined a cutoff value of 143.50 cm/s with respect to stroke risk in a sample with HbSC very similar to the present study. Using this value, 60 children with HbSC had low TAMMV, while 8 children had high TAMMV.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Vieira and colleagues [ 10 ] defined a cutoff value of 143.50 cm/s with respect to stroke risk in a sample with HbSC very similar to the present study. Using this value, 60 children with HbSC had low TAMMV, while 8 children had high TAMMV.…”
Section: Resultssupporting
confidence: 67%
“…Previous studies have evaluated individuals with HbSC and described an average TAMMV of 94 cm/s and 104.9 ± 19.3 cm/s [ 9 , 10 ]. In our study, we found that children with HbSC had an average TAMMV of 114.31 ± 22.72 cm/s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have demonstrated that children with HbSC disease have significantly lower TCD velocities in MCA and ICA compared to children with SCA. A recent large Brazilian study has estimated the mean MCA TAMMV in HbSC disease to be 104 cm/s, with strong negative correlation with haemoglobin levels and haematocrit (Vieira et al , ) compared to mean MCA TAMMV of 129 cm/sec in a study of 190 HbSS patients (Adams et al , ). A smaller study in London reported a mean MCA velocity of 94 cm/s in HbSC patients with a significant positive correlation with platelet counts.…”
Section: Tcd In Hbscmentioning
confidence: 99%